2010
DOI: 10.1111/j.1744-7348.2010.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Clone differentiation and varietal identification by means of SSR, AFLP, SAMPL and M‐AFLP in order to assess the clonal selection of grapevine: the case study of Manto Negro, Callet and Moll, autochthonous cultivars of Majorca

Abstract: Clonal selection is the most worldwide spreading method to improve the performance of wine grapevine (Vitis vinifera) cultivars. In the special case of autochthonous varieties with only local interest, such as Manto Negro, Callet and Moll in Majorca (Spain), good knowledge of their genotypic resources is helpful to assess the development of viticultural and enological potentialities. In this study, 94 vines (including Manto Negro, Callet, Moll and wrongly identified samples) were analysed by means of genetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…Genomic DNA (500 ng) was digested and ligation was performed in 4 h at 37°C using EcoRl (or Pstl) and Msel enzymes (5 U each), 1 U of T4 ligase, 50 pmol of Mseladaptor, 5 pmol of £coRI-adaptor (or Pstl) in 1 x RL buffer (20 mM Tris-acetate, 20 mM magnesium acetate, 100 mM potassium acetate, 5 mM DTT, 2.5 mg BSA) added with ATP to a final concentration of 10 mM [36]. Then, 5 ul of seven-fold diluted digested and ligated DNA was preamplified in 20 ul reaction mixture containing 75 ng of EcoRl + N (or Pstl + N) and Msel + N primers, lx PCR buffer (50 mM MgCl, 1.5 mM MgCl 2 , 10 mM Tris-HCl), 10 mM dNTPs and 1 U of Taq DNA polymerase [39]. The Eco, Pst and Mse primers were called in tables and figures as E, P and M, respectively.…”
Section: Aflp Sampl and M-aflp Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Genomic DNA (500 ng) was digested and ligation was performed in 4 h at 37°C using EcoRl (or Pstl) and Msel enzymes (5 U each), 1 U of T4 ligase, 50 pmol of Mseladaptor, 5 pmol of £coRI-adaptor (or Pstl) in 1 x RL buffer (20 mM Tris-acetate, 20 mM magnesium acetate, 100 mM potassium acetate, 5 mM DTT, 2.5 mg BSA) added with ATP to a final concentration of 10 mM [36]. Then, 5 ul of seven-fold diluted digested and ligated DNA was preamplified in 20 ul reaction mixture containing 75 ng of EcoRl + N (or Pstl + N) and Msel + N primers, lx PCR buffer (50 mM MgCl, 1.5 mM MgCl 2 , 10 mM Tris-HCl), 10 mM dNTPs and 1 U of Taq DNA polymerase [39]. The Eco, Pst and Mse primers were called in tables and figures as E, P and M, respectively.…”
Section: Aflp Sampl and M-aflp Analysismentioning
confidence: 99%
“…In order to detect intravarietal genetic variability, AFLP, SAMPL and M-AFLP molecular markers were used [39]. Analyses were performed by Starlet liquid handling workstations (Hamilton), ABI-3130XL capillary sequencer (Applied Biosystems) and ALFexpress-II semi-automated gel sequencer (Amersham).…”
Section: Aflp Sampl and M-aflp Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Factor vineyard can include in its complexity many parameters related to soil, management and microclimate. Cretazzo et al (2010c) showed that Moll vines presented a high genetic similarity among appellations and vineyards of Majorca. Therefore, it is expected that grape plant effects on vine parameters are more linked to virus infection than to intravarietal genetic variability.…”
Section: Analysis Of the Factors Influencing Yield Sugarmentioning
confidence: 99%